2015
DOI: 10.1080/1745039x.2015.1075669
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a negative energy balance induced by feed restriction in lactating sows on hepatic lipid metabolism, milk production and development of litters

Abstract: In rodents, forced activation of hepatic peroxisome proliferator-activated receptor α (PPARα) by administration of exogenous PPARα activators during lactation leads to a reduction of milk triacylglycerol (TAG) production. Herein, we investigated whether a negative energy balance (NEB) induced by feed restriction (about 18% lower feed and energy intake) during lactation by increasing the release of fatty acids, which act as PPARα agonists, causes a disruption of hepatic lipid metabolism and thereby impairs milk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 30 publications
0
13
0
Order By: Relevance
“…It may be due to the role of resveratrol in energy metabolism. Resveratrol, a natural compound, has been reported to affect energy metabolism and mitochondrial function and to serve as a calorie restriction mimetic (Gessner et al, ). In addition, previous studies have reported that resveratrol supplementation reduced liver fat accumulation and increased rates of fatty acid oxidation and promoted the release of energy (Forouzan, Azita, & Payman, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It may be due to the role of resveratrol in energy metabolism. Resveratrol, a natural compound, has been reported to affect energy metabolism and mitochondrial function and to serve as a calorie restriction mimetic (Gessner et al, ). In addition, previous studies have reported that resveratrol supplementation reduced liver fat accumulation and increased rates of fatty acid oxidation and promoted the release of energy (Forouzan, Azita, & Payman, ).…”
Section: Discussionmentioning
confidence: 99%
“…It may be due to the role of resveratrol in energy metabolism. Resveratrol, a natural compound, has been reported to affect energy metabolism and mitochondrial function and to serve as a calorie restriction mimetic (Gessner et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Using bovine mammary epithelial cells (BMEC) in vitro, Liu et al, showed that increasing glucose availability may increase the synthesis of milk fat and lactose by modulating the mRNA expression of key genes and subsequently affect the synthesis of milk composition . On the other hand, restriction of macronutrients during lactation results in a decrease of mRNA concentrations of sterol regulatory element-binding protein target genes involved in lipid synthesis in the liver along with plasma concentration of TAG (Gessner et al, 2015) which may regulate the milk production in lactating pigs. Several of milk traits (milk production, acidity, milk stability etc.)…”
Section: Milk Productionmentioning
confidence: 99%
“…Maternal milk is widely considered the best feeding source for newborns compared with the alternatives (1)(2)(3) , even in the setting of maternal undernutrition during pregnancy and lactation, which not only affects maternal health but negatively programmes neonatal growth and organ development and maturation (4)(5)(6)(7)(8) . Reduced maternal nutrition is the most extensively studied programming challenge of offspring phenotypic plasticity (9) .…”
mentioning
confidence: 99%